A guide to reference books for Japanese studies (International House of Japan Library, 1997)
This bibliographical guide is intended for the use of persons in both categories, to familiarize them with the variety of reference works in English and Japanese. Such reference works should serve to facilitate and advance Japanese studies in the humanities and the social sciences.